Odpowiedzi

2010-03-03T23:48:38+01:00
A-2b+a+3b=2a+b
3/4a-3/4b-1/8a-1/8b=6/8a+6/8b-1/8a-1/8b=5/8a+5/8b
-0,2a-0,5b-0,6a+0,8b=-0,2a+0,3b
7/12(3/21a+4/21b)+9/10(2/6a-5/6b)=1/12a+1/9b+3/10a+3/4b
1/12a-1/8b-1/24a-1/4b=1/12a-3/8b
2010-03-03T23:49:42+01:00
A)½(2a-4b)+⅓(3a+9b) = 1a - 2b +1a + 3b = 2a + b
b)¾(a-b)-⅛(a+b) = ¾a - ¾b - ⅛a - ⅛b = ⅝a - ⅝b
c)0,1(4a-5b)-0,2(3a+4b) = 0,4a - 0,5b - 0,6a - 0,8b = - 0,2 - 1,3b
d)⁷/₁₂(¹/₇a+⁴/₂₁b)+⁹/₁₀(⅓a-⅚b) = ¹/₁₂a + ⁷/₆b + ³/₁₀a - ³/₅b = ²³/₇₀a - ¹⁷/₃₀b
e)¹/₁₈(³/₂a-⁹/₄b)-¹/₃₂(⁴/₃a-8b) = ¹/₁₂a - ¹/₈b - ¹/₂₄a - ¼b = ¹/₁₂a - ³/₈

2010-03-04T00:00:16+01:00
A)½(2a-4b)+⅓(3a+9b)= a-2b+a+3b= 2a+b
b)¾(a-b)-⅛(a+b)= ¾a-¾b-½a-½b= ¼a-1¼b
c)0,1(4a-5b)-0,2(3a+4b)= 0,4a-0,5b-0.6a-0,8b= -0,2a-13b
d)⁷/₁₂(¹/₇a+⁴/₂₁b)+⁹/₁₀(⅓a-⅚b)= ¹/₁₂a+¹/₁₂b+³/₁₀a-¾b= ⁵/₆₀a+⁵/₆₀b
+¹⁸/₆₀a-⁴⁵/₆₀b= ²³/₆₀a-⁴⁰/₆₀b=
e)¹/₁₈(³/₂a-⁹/₄b)-¹/₃₂(⁴/₃a-8b)= ¹/₁₂a- ⅛b-¹/₂₄a+¼b= ²/₂₄a-⅛b-
¹/₂₄a+²/₈b= ¹/₂₄a+⅛b
1 5 1